Estimation of Technical Efficiency of Micro and Small-Scale Manufacturing Enterprises in Selected Towns of Jimma Zone, Oromia National Regional State - Haile Girma; Gadisa Abera Dinka; Mohammedsani Ali Gelan (Journal of Economics and Behavioral Studies, 2019)
This study was conducted to estimate the technical efficiency of micro and small-scale manufacturing enterprises in Selected Towns of Jimma Zone, Oromia National Regional State by using the Stochastic Frontier Approach. The analysis used Cross-sectional data which was collected from 343 Micro and small-scale manufacturing enterprises in 2018. The finding shows the mean technical efficiency of sampled Micro and Small-Scale Manufacturing Enterprises is about 54.8% and output value-added is positively affected by capital input and raw material, but negatively affected by labor input. The finding from the inefficiency model indicates that technical inefficiency of sampled Micro and Small-Scale Manufacturing Enterprises is negatively affected by the amount of finance used for initial investment expenses; lower for enterprises which received land from the government, participate only in “Ekub”, participate in both “Ekub” and “Edir”. However, seasonal change in demand for a product is found to make technical inefficiency of enterprises higher. Thus, by improving Micro and Small-Scale Manufacturing Enterprises access to land, market, sufficient